Comparative chromosome mapping of 5S rDNA and 5SHindIII repetitive sequences in Erythrinidae fishes (Characiformes) with emphasis on the Hoplias malabaricus 'species complex' - Ferreira, I. A.; Bertollo, L. A. C.; Martins, C. (Karger, 2007)
Chromosomal localization of 5S rDNA and 5SHindIII repetitive sequences was carried out in several representatives of the Erythrinidae family, namely in karyomorphs A, D, and F of Hoplias malabaricus, and in H. lacerdae, Hoplerythrinusunitaeniatus and Erythrinus erythrinus. The 5S rDNA mapped interstitially in two chromosome pairs in karyomorph A and in one chromosome pair in karyomorphs D and F and in H. lacerdae. The 5SHindIII repetitive DNA mapped to the centromeric region of several chromosomes (18 to 22 chromosomes) with variations related to the different karyomorphs of H. malabaricus. on the other hand, no signal was detected in the chromosomes of H. lacerdae, H. unitaeniatus and E. erythrinus, suggesting that the 5SHindIII-DNA sequences have originated or were lost after the divergence of H. malabaricus from the other erythrinid species. The chromosome distribution of 5S rDNA and 5SHindIII-DNA sequences contributes to a better understanding of the mechanisms of karyotype differentiation among the Erythrinidae members.Copyright (c) 2007 S. Karger AG, Basel.